Quality management : tools, methods, and standards - Sartor, Marco; Orzes, Guido (Emerald Publishing Limited, 2019)
The book describes the most important quality management tools (e.g. QFD, Kano model), methods (e.g. FMEA, Six Sig-ma) and standards (e.g. IS0 9001, ISO 14001, ISO 27001, ISO 45001, SA8000). It reflects recent developments in the field. It is considered a must-read for students, academics, and practitioners.- Resumé vydavatel
Includes index.
Keywords: management jakosti; quality control; elektronické knihy; kolektivní monografie; electronic books; collective monographs